Localization of Rolling Stock within the Railway Network Model utilizing of Web Services - Fikejz, Jan; Brožek, Josef (IEEE (Institute of Electrical and Electronics Engineers), 2016)
This article deals with a design of a railway infrastructure model which is designed as a data structure non-oriented graph. The railway infrastructure model is implemented by the database Oracle Spatial, utilizes the Network Data Model module. Further attention is paid to localization of the rolling stock and the searching algorithm of the previous or next railway station. The last part pays attention to using of web services for the localization of rolling stock and the description of testing mobile applications. For testing a support tools with a core of discrete simulation is used.
Lokalizace kolejových vozidel v rámci modelu železniční sítě s využitím webového servisu
Keywords: Localization; Rolling; Stock; within; the; Railway; Network; Model; utilizing; Web; Services; Lokalizace; kolejových; vozidel; rámci; modelu; železniční; sítě; využitím; webového; servisu